Hemophilia: Homeostasis and exercise - Pravatto, Alexandra (2011)
The hemophilia is a disorder in the mechanism of blood coagulation that can result in uncontrollable hemorrhages. It is a genetic-hereditary deficiency, almost exclusive male, with occurrence of a case in each ten thousand inhabitants. Although diverging about the positive and negative factors of the physical activity on the mechanisms of platelet aggregation, coagulation and fibrinolysis, all of the researched authors were unanimous in affirming that the swinging between advantages and obstacles is positive. They still agree in affirming that more studies would be necessary to remove more contusing conclusions. Mirroring those results to the specifies conditions of the hemophiliacs it is possible that they get some improvements on your life with the results of those researches, so much in the part to muscle-articulate as well as in the coagulation part and bleeding control. Once proven that the exercise can in some way stimulate the factor VIII, the exercise can became an important tool for the handling of the disease. Fact is that the totality of the few studies demonstrated a deficiency in the coefficients: forces, mobility and proprioception of that population.